2015
DOI: 10.1210/en.2014-1467
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate-Induced Impairments of β-Cell Function Are Linked With Generation of Specific Ceramide Species via Acylation of Sphingosine

Abstract: Prolonged exposure to palmitate impairs β-cell function and mass. One of the proposed mechanisms is alteration in ceramide (Cer) generation. In the present study, exposure to palmitate induced the level of palmitoyl transferase and Cer synthases, enzymes of the Cer de novo and salvage pathways, and doubled total Cer levels, which was associated with decreased insulin secretion and augmented apoptosis in MIN6 cells and human islets. By inhibiting enzymes of the pathways pharmacologically with myriocin (ISP-1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 34 publications
6
54
0
3
Order By: Relevance
“…Second, SPH can be acylated to ceramide via salvage synthesis pathway. It was reported that exposure of mouse pancreatic beta-cell to Palm induced the level of ceramide synthase, the enzyme of the ceramide salvage pathway, which promoted the conversion of SPH to ceramide [26]. Therefore, we speculate that inhibition of NCDase activity and stimulation of SPH converting to ceramide after Palm treatment might lead to non-obvious increase in SPH, inconsistent with the increase in ceramide.…”
Section: Discussionmentioning
confidence: 78%
“…Second, SPH can be acylated to ceramide via salvage synthesis pathway. It was reported that exposure of mouse pancreatic beta-cell to Palm induced the level of ceramide synthase, the enzyme of the ceramide salvage pathway, which promoted the conversion of SPH to ceramide [26]. Therefore, we speculate that inhibition of NCDase activity and stimulation of SPH converting to ceramide after Palm treatment might lead to non-obvious increase in SPH, inconsistent with the increase in ceramide.…”
Section: Discussionmentioning
confidence: 78%
“…IL-6 is thought to be involved in the metabolic link between ceramide, insulin resistance and inflammation [20]. Furthermore, the accumulation of ceramide has been demonstrated to be detrimental to pancreatic beta cells [21][22][23] and may, therefore, play a direct role in the pathogenesis of type 2 diabetes. Alkenylphosphatidylethanolamines (plasmalogens) contain a vinyl ether linkage that is particularly susceptible to oxidation by reactive oxygen species, and as such they are proposed to play an antioxidant role in membranes and lipoproteins [24].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis induced by ELOVL2 downregulation potentiated ceramide accumulation during glucolipotoxicity and was completely abolished by inhibition of de novo ceramide synthesis. Glucolipotoxicity has been shown to induce the formation of ceramides with specific N-acyl chain lengths rather than an overall increase in ceramide content [20,35]. We found that DHA blocked the accumulation of pro-apoptotic ceramide species induced by glucolipotoxicity.…”
Section: Discussionmentioning
confidence: 56%